Fertilisers Use and Choices by Farmers: A Comparative Study between Chemical vs Organic Fertilisers - SRIVASTAV, SHASHANK (International Journal of Psychosocial Rehabilitation, 2024)
Fertilisers are critical to increasing crop output and maintaining agricultural production. Farmers may choose from a variety of fertilisers for their crops, ranging from chemical to organic fertilisers. In this comparative research, we looked at how farmers use and choose fertilisers in different parts of the world. We polled farmers who use chemical and organic fertilisers to determine the advantages and disadvantages of each type of fertiliser. According to our findings, chemical fertilisers produce faster and larger yields in the near term, but organic fertilisers provide more long-term advantages, such as soil health and environmental sustainability. Nevertheless, fertiliser selection is influenced by a variety of factors such as crop type, soil type, weather conditions, availability, and affordability. We conclude that a balanced strategy is required to achieve sustainable agriculture and environmental protection